R&D: who does the R, who does the D? - Cadot, Olivier; Desruelle, Dominique (Journal of International Economics, 1998)
An examination of the determinants of the allocation of national research and development (R and D) resources between research and development activities is conducted. A preemption equilibrium is constructed and related to hypotheses concerning home market size and the cost and characteristics of an international R and D race. A two-sector model of resource allocation is presented to demonstrate that two effects, a fairly mechanical resource-allocation effect and a strategic effect, are employed when one country is larger than the other.